2014
DOI: 10.4049/jimmunol.1400849
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Regulate Immune Response in Patients with Chronic Hepatitis B Virus Infection through PD-1–Induced IL-10

Abstract: Although myeloid-derived suppressor cells (MDSCs) are well known for their immunosuppressive function in several pathological conditions, the role of MDSCs in hepatitis B virus infection remains obscure. In this study, we investigated the frequency and function of MDSCs in the peripheral blood and liver of 91 chronic hepatitis B (CHB) patients. A higher percentage of MDSCs, defined as CD14+HLA-DR−/low, was detected in peripheral blood of CHB patients than that of the healthy controls. Moreover, high expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 45 publications
3
81
1
Order By: Relevance
“…Our studies are not consistent with the observations of Huang et al (9), who found no correlation between HBsAg levels and MDSC numbers. However, their findings may have resulted from the definition of their population of MDSCs as CD14 + HLA-DR 2/low , whereas we defined mMDSCs by four markers as described.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our studies are not consistent with the observations of Huang et al (9), who found no correlation between HBsAg levels and MDSC numbers. However, their findings may have resulted from the definition of their population of MDSCs as CD14 + HLA-DR 2/low , whereas we defined mMDSCs by four markers as described.…”
Section: Discussioncontrasting
confidence: 99%
“…These cells have been shown to suppress HBV-specific CD8 + T cell responses (9). However, the mechanisms involved in the expansion of MDSCs in patients with CHB have not been identified.…”
Section: /Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that liver is one of the major sites of MDSCs, in addition to the immune organs (28). Accumulation of MDSC in liver has been observed in tumor-bearing hosts, hepatitis B virus-infected individuals, and high fat dietfed animals (4,29,30). Also, hepatic stellate cells were reported to support the expansion of MDSCs in vitro (31).…”
Section: Discussionmentioning
confidence: 99%
“…One striking finding of this study is that there are significant correlations between the levels of antigenstimulated cIL-10 production in PBMC and RhCMV genome copy numbers detected in saliva. This is not unique to RhCMV, as cIL-10 levels have been positively associated, either alone or with other biomarkers, with increased burdens of other pathogens, including human papillomavirus, HIV, hepatitis B virus, EpsteinBarr virus (EBV), Mycobacterium tuberculosis, Leishmania spp., dengue virus, and murine and human CMV (45,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72). While the specific cell type(s) responsible for elevated cIL-10 expression in response to RhCMV antigen exposure was not explored, multiple cell types have been implicated for other pathogens, including regulatory B and T cells.…”
Section: Discussionmentioning
confidence: 99%